Comparison of growth rates and epiphytic load of three species of seagrasses enhalus acoroides (L.f.) royle, halodule uninervis (Forsk.) aschers. and Thalassia hemoprichii (Ehrenberg) aschers. in Kalaparan, Taklong Island National marine Reserve, Nueva Valencia, Guimaras. - Sedonio, Rosie Joan J. (1994.)
Growth rates of Enhalus acoroides, Halodule uninervis and Thalassia hemprichii in 24 hours and epiphytic load were determined and compared. Leaf marking technique was employed in monitoring the incremental growth. This was done on February 6-7, 1993 in Kalaparan, Taklong Island National Marine Reserve, Nueva Valencia, Guimaras., Results obtained on the growth rates of the three seagrass species mentioned above showed that, E. acoroides grew fastest (7.0 mm/day), H. uninervis was second (6.0 mm/day) and T. hemprichii (5.0 mm/day) was the slowest. There was highly significant difference in growth rates among the three species (P < 0.001). Epiphytic load, which was found heaviest at the apical region of the leaf blades appear to be a direct effect of tides and the growth activity of the leaf itself, exposure to higher light intensities and presumably a much greater nutrient supply. The seagrass community was dominated largely by red algae and diatoms. Epiphytic load had no definite pattern in relation to growth rates of seagrasses.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Seagrasses -- Kalaparan, Guimaras